A DNA macro-array to simultaneously identify 32 meat species in food samples. (September 2016) - Cottenet, Geoffrey; Sonnard, Véronique; Blancpain, Carine; Ho, Hui Zhen; Leong, Hann Lum; Chuah, Poh Fong
Abstract: Considering the recent cases of meat adulteration and fraud, efficient and accurate analytical methods are needed for the specific identification of meat species as a key importance to maintain consumers' trust and to comply with various local labelling legislations. As a reference approach, the application of PCR to meat speciation is always limited to few species, whereas there is a strong need to broaden the number of identified meat species. PCR was here associated with a commercial DNA macro-array spotted with meat-specific capture probes, allowing the simultaneous identification of 32 meat species on 8 samples per chip support. Tested on pure meat samples, spiked samples, proficiency test samples, and processed samples, the method showed high specificity on the targeted species and allowed a sensitivity down to 1% (w/w). Easy-to-use, fast and cost-efficient, this multi-screening approach is fit-for-purpose as a tool to detect meat substitution or adulteration for meat testing laboratories. Highlights: This DNA macro-array allows the simultaneous identification of 32 meat species. Up to 8 samples can be analysed per chip support. The method showed a sensitivity of 1% in adulterated spiked meat samples. Meat mislabelling can be easily detected.